2014
DOI: 10.1088/0004-637x/787/1/54
|View full text |Cite
|
Sign up to set email alerts
|

DISTANCE AND PROPER MOTION MEASUREMENT OF WATER MASERS IN SHARPLESS 269 IRS 2w

Abstract: We present astrometric analysis of archival data of water masers in the starforming region Sharpless 269 (S269) IRS 2w, observed with the VLBI Exploration of Radio Astrometry. An annual parallax of one of the bright maser features in this region was previously reported to be 0.189 ± 0.008 milliarcsecond (mas) using part of the same archival data as we used. However, we found that this maser feature is not the best to represent the annual parallax to S269 IRS 2w because the morphology is remarkably elongated in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 25 publications
(28 reference statements)
4
20
1
Order By: Relevance
“…The strongest maser spot was detected in all sixteen epochs with a flux density maximum of 95.8 Jy beam −1 at epoch H. This spot has a distinctive elongated shape at all epochs (see Fig. 1), as was firstly reported by Miyoshi et al (2012) and highlighted by Asaki et al (2014). The spot varies somewhat over time but retains its basic shape throughout all our observations.…”
Section: Elongated Water Maser Emissionsupporting
confidence: 84%
See 1 more Smart Citation
“…The strongest maser spot was detected in all sixteen epochs with a flux density maximum of 95.8 Jy beam −1 at epoch H. This spot has a distinctive elongated shape at all epochs (see Fig. 1), as was firstly reported by Miyoshi et al (2012) and highlighted by Asaki et al (2014). The spot varies somewhat over time but retains its basic shape throughout all our observations.…”
Section: Elongated Water Maser Emissionsupporting
confidence: 84%
“…Later Miyoshi et al (2012) and Asaki et al (2014) disputed the distance to S 269 reported by Honma et al (2007) , firstly pointing out that kinematic and optical photometric distance estimates reported shorter values (3.7-3.8 kpc, see Moffat et al 1979;Wouterloot & Brand 1989;Xu et al 2009). Moreover, they reanalyzed the VERA data specifically using more compact maser spots than those used by Honma et al (2007), and reported a parallax value 0.247 ± 0.034 mas, which corresponds to a distance of 4.05 +0.65 −0.49 kpc (Asaki et al 2014). The tension between the two parallax distances is crucial for two reasons.…”
Section: Introductionmentioning
confidence: 94%
“…Anyhow, it is possible to use maser spots for measuring distances by the trigonometric parallax method (see observational review in Reid & Honma (2014) and theoretical considerations in Sobolev & Gray (2012); Sobolev et al (2008)), though in the normally avoided cases of the complicated spot structure this method can bring incorrect results, Asaki et al (2014). This precise method is successfully used in the studies of the spiral structure of the Galaxy when the number of sources is large enough (error is less than 10% for determination of parameters with 500 sources, Honma et al (2015)).…”
Section: Introductionmentioning
confidence: 99%
“…The images were made with DIFMAP using CLEAN and a self-calibration technique. The above process using phase-referencing data greatly improve the image quality for 3C 66B, making it possible to image very weak extended jets, as reported by Asaki et al (2014) for water maser mapping. We cannot find a significant counterjet component at any epoch, in contrast with previous lower frequency results (Giovannini et al 2001;Kharb et al 2009).…”
Section: Observations and Data Reductionmentioning
confidence: 91%